New soluble magnesium-based alloys for use in traumatology - Chorny, Vadim; Yatsun, Yevgeniy; Golovakha, Maksim; Shalomeev, Vadim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective:to develop a new magnesium-based alloy with physical and chemical properties that allow to use it for osteosynthesis. Methods:we developed prototypes by doping the silver standard and scandium alloys based on magnesium ML-5 and ML-10. Studied their strain, macro-and microstructure by light surface microscopic metallographic analysis. The rate of dissolution of magnesium alloys studied in physiological solutions with various sodium chloride (NaCl, Helofuzyn, Venofundyn). Results:mechanical tests have shown that microalloying alloys ML-5 and ML-10 silver and scandium increased their strength and ductility. Established that the dissolution rate of magnesium alloys depending on their chemical composition and structure may change more than 500 times. The study of solubility in alloy ML-10 Helofuzyni allowed to establish that the optimal content of silver in the alloy can be 0.05–0.07 % by weight, as increased its content to 1.0 % almost does not change the average rate of solubility. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> increased physical and mechanical properties of magnesium alloys and regulated their dissolution in physiological solutions provided input into the composition of silver or scandium. This found that the optimal content of these elements in magnesium alloy is in the range 0.05– 0.1 % (wt.). ML<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">-<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">10 strength alloy containing 0.05 % silver, more than 2 times exceeds the strength of bone man. At the macro and mikroriv-not studied the process of dissolution of magnesium alloy with silver ML<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">-<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">10 in Venofundyni and determined the speed of the metal in it. Duration properties preserving strong magnesium alloy ML<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: EN-US; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;" lang="EN-US">-<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">10 during contact with physiological solution can be significantly increased by changing parameters such as geometry and thickness of the metal.